Initial Experience with Aortic Valve Replacement via a Minimally Invasive Approach: A Comparison of Stented, Stentless and Sutureless Valves - Konertz, Johanna (Med Sci Monit, 2017)
BACKGROUND: This study aimed to compare the short-term outcomes of MIS-AVR among 3 different types of biological heart valves. MATERIAL/METHODS: Complete data were obtained from 79 patients who underwent MIS-AVR between January 2010 and June 2015. Patients were divided into 3 groups: 27 patients (group A) received Medtronic 3f(®) (Medtronic Inc., Fridley, MN, USA), 36 patients (group B) received DokimosPlus(®) (LabCor Laboratórios Ltda., Belo Horizonte, Brazil) and 16 patients (group C) received Perceval(®) (Sorin Biomedica Cardio S.r.l., Saluggia VC, Italy) valves. Operative and postoperative parameters such as duration of operation, bypass time, duration of ventilation, morbidity, and mortality were statistically analyzed using the Kruskal-Wallis test. Hemodynamic assessment with transthoracic echocardiography was performed before discharge. RESULTS: The EuroSCORE II ranged between 0.67 and 6.94 with no significant difference between the groups. The median operative time was 166 min (range 90–230 min) in total, with significantly shorter times in group C (120 min [range 90–200]). The median total ventilation time was significantly lower in group C and significantly higher in group A. Hemodynamic evaluation demonstrated a mean maximal velocity (v(max)) over the aortic valve of 2.3 m/s (range 0.9–4.3 m/s) with average mean and peak pressure gradient values of 10 mmHg (range 3–24 mmHg) and 20 mmHg (range 5–42 mmHg), respectively. Group A showed the highest values for v(max) (H>5.99). No significant difference was found regarding duration of hospitalization. Mortality was 3%. CONCLUSIONS: In conclusion, all 3 valves showed good perioperative results, satisfying hemodynamic performance, and low complication rates.